PENGARUH KARAKTERISTIK INDIVIDU DAN KOMUNIKASI INTERNAL TERHADAP KINERJA KARYAWAN - Fitri Hariyanti ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2021)
The decline on employee performance is due to they are not able to reach targets as required by company. They must be decided by the company because they have poor performance such as sales, who did not reach the target during the trial period. Employees who are not conscientious, employees who are not alert in Â working, for example handling tasks that cannot be done in a predetermined time. This research took a sample of 42 respondents by using the total sampling technique. The data collection technique is done through observation and questionnaires. The data analysis technique is multiple linear regressions. Then also wll tested, such as validity test, reliability test, classical assumption test followed by hypothesis testing.The results showed that there was an effect of individual characteristics (X1) on employee performance (Y) at PT. Genta Lampung Makmur Bengkulu, it was to 0,000, thus Ho was rejected and Ha was accepted. The significance value of variable X has an effect on employee performance (Y). Thenalso, the effect of internal communication (X2) on employee performance, with its value 0.031, thus Ho is rejected and Ha is accepted. From these significance values obtained, the variable X2 has an effect on employee performance (Y). Individual characteristics and internal communication simultaneously have an effect on employee performance with a value of F_sig <Î± where F_sig is 0,000.Â Keywords: Individual Characteristics, Internal Communication, Performance.